2022
DOI: 10.3389/fcvm.2022.935705
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High-Power and Very High-Power Short-Duration Radiofrequency Ablation on Procedure Characteristics and First-Pass Isolation During Pulmonary Vein Isolation

Abstract: IntroductionHigh-power short-duration (HPSD) radiofrequency ablation has been proposed to produce rapid and effective lesions for pulmonary vein isolation (PVI). We aimed to evaluate the procedural characteristics and the first-pass isolation (FPI) rate of HPSD and very high-power short-duration (vHPSD) ablation compared to the low-power long-duration (LPLD) ablation technique.MethodsOne hundred fifty-six patients with atrial fibrillation (AF) were enrolled and assigned to LPLD, HPSD, or vHPSD PVI. The energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…In a similar study, Salló et al compared 30, 50, and 90 W approaches 14 . The investigators reported similar FPI rates between 50 and 90 W (78% vs. 80%).…”
Section: Clinical Outcomes With 90 W Ablationmentioning
confidence: 96%
“…In a similar study, Salló et al compared 30, 50, and 90 W approaches 14 . The investigators reported similar FPI rates between 50 and 90 W (78% vs. 80%).…”
Section: Clinical Outcomes With 90 W Ablationmentioning
confidence: 96%
“…Thus, the final analysis included 29 studies 8,24–51 (3 randomized studies and 26 observational studies), analyzing 9721 patients. vHPSD ablation was performed in five studies (four studies with 90‐W ablation and one study with 70‐W ablation).…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8] These properties of vHPSD lesions raise a need for decreasing the interlesion distance, verified in a clinical setting by our previous report. 11 The advantages of this novel technique have also translated into clinically meaningful results in previous studies, as evidenced by substantially shorter total procedure, LA ablation, and radiofrequency times compared with ablation with lower power. 11,13 Our current study strongly underpins these findings, as procedures performed with 90 W were shorter than those with 50 W. Nevertheless, acute procedural efficacy outcome measures of vHPSD PVI have previously shown a huge variety; for example, first-pass isolation rates ranged from 18% to 80% and acute reconnection rates ranged from 27% to 32%.…”
Section: Vhpsd Pvimentioning
confidence: 90%
“…11 The advantages of this novel technique have also translated into clinically meaningful results in previous studies, as evidenced by substantially shorter total procedure, LA ablation, and radiofrequency times compared with ablation with lower power. 11,13 Our current study strongly underpins these findings, as procedures performed with 90 W were shorter than those with 50 W. Nevertheless, acute procedural efficacy outcome measures of vHPSD PVI have previously shown a huge variety; for example, first-pass isolation rates ranged from 18% to 80% and acute reconnection rates ranged from 27% to 32%. 10,11,13 Studies that showed low first-pass isolation and high acute reconnection rates used larger (<6 mm) inter-tag distance, which explains the difference from our current results.…”
Section: Vhpsd Pvimentioning
confidence: 90%
See 1 more Smart Citation